Enzyme-Mediated Quenching of the Pseudomonas Quinolone Signal (PQS) Promotes Biofilm Formation of Pseudomonas aeruginosa by Increasing Iron Availability - Tettmann, Beatrix; Niewerth, Christine; Kirschhöfer, Frank; Neidig, Anke; Dötsch, Andreas; Brenner-Weiss, Gerald; Fetzner, Susanne; Overhage, Joerg (Frontiers in Microbiology, 2016)
The 2-alkyl-3-hydroxy-4(1H)-quinolone 2,4-dioxygenase HodC was previously described to cleave the Pseudomonas quinolone signal, PQS, which is exclusively used in the complex quorum sensing (QS) system of Pseudomonas aeruginosa, an opportunistic pathogen employing QS to regulate virulence and biofilm development. Degradation of PQS by exogenous addition of HodC to planktonic cells of P. aeruginosa attenuated production of virulence factors, and reduced virulence in planta. However, proteolytic cleavage reduced the efficacy of HodC. Here, we identified the secreted protease LasB of P. aeruginosa to be responsible for HodC degradation. In static biofilms of the P. aeruginosa PA14 lasB::Tn mutant, the catalytic activity of HodC led to an increase in viable biomass in newly formed but also in established biofilms, and reduced the expression of genes involved in iron metabolism and siderophore production, such as pvdS, pvdL, pvdA and pvdQ. This is likely due to an increase in the levels of bioavailable iron by degradation of PQS, which is able to sequester iron from the surrounding environment. Thus, HodC, despite its ability to quench the production of virulence factors, is contraindicated for combating P. aeruginosa biofilms.